Kinetics and Efficiency of Triplet‐Triplet Annihilation Photon Upconversion under Pulsed Excitation Conditions. Issue 1 (18th November 2020) - Ye, Chen; Albinsson, Bo; Börjesson, Karl
Abstract: Triplet‐triplet annihilation is a promising method to convert low energy photons to high energy ones. Due to the long time‐scales and the bimolecular nature of the process, the overall efficiency of triplet‐triplet annihilation greatly depends on the excitation type and intensity. Upconversion efficiencies are usually measured using continuous wave conditions. Here we develop an analytical and experimental method to investigate how the excitation modulation affects the triplet‐triplet annihilation efficiency. The simulated and experimental results demonstrate high consistency. The triplet‐triplet annihilation efficiency drops as expected with increasing excitation frequency at a fixed average power density, which our simulations accurately predicts. The method described here allows to relate efficiencies measured at pulsed conditions with those measured at continuous wave conditions. Abstract : Efficient photon upconversion with a pulsed laser : The triplet‐triplet annihilation photon upconversion efficiency is strongly dependent on the excitation frequency. We herein provide a method to correlate the photon upconversion intensity to the repetition rate of the light source. The model was confirmed by experiments using modulated laser excitation.